Clickbait - Nicole Patten; Ricky Telg; Kevin Kent (EDIS)
This publication provides an overview of clickbait and its characteristics. The publication also discusses a few implications of clickbait use. Written by Nicole Patten, Ricky Telg, and Kevin Kent, and published by the UF/IFAS Department of Agricultural Education and Communication, March 2024.